The eagle kite : a novel - Fox, Paula (New York : Orchard Books, 1995)
Liam's father has AIDS, and his family cannot talk about it until Liam reveals a secret that he has tried to deny ever since he saw his father embracing another man at the beach.
Keywords: Homosexuality -- Fiction; AIDS (Disease) -- Fiction; Gay fiction